Revised Values for the Parameters of the Sets Technique for Monitoring the Incidence Rate of a Rare Disease - Chen, Rina (Methods of Information in Medicine, 1986)
Values recommended for the parameters of the sets technique are presented. These values are more accurate than the ones published earlier. The values are determined so as to enhance the detection of small levels of increase in the rate of a rare event.
Keywords: Monitoring System; Sets Technique; Cancer Diseases; Birth Defects